2019
DOI: 10.1186/s13561-019-0228-8
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket payments in the context of a free maternal health care policy in Burkina Faso: a national cross-sectional survey

Abstract: BackgroundIn April 2016, Burkina Faso introduced a free health care policy for women. Instead of reimbursing health facilities, as many sub-Saharan countries do, the government paid them prospectively for covered services to avoid reimbursement delays, which are cited as a reason for the persistence of out-of-pocket (OOP) payments. This study aimed to (i) estimate the direct expenditures of deliveries and covered obstetric care, (ii) determine the OOP payments, and (iii) identify the patient and health facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 30 publications
7
55
2
Order By: Relevance
“…Previous research has also reported that cultural factors such as women's delivery preferences and how the placenta is handled after the birth can significantly influence women's decisions on place of delivery [35,38,43]. In the present study, a common theme that emerged was that health facilities were not supportive of women's delivery preferences (i.e., squatting) and as a result, women did not feel that they could or that they wanted to deliver at these facilities.…”
Section: Social and Cultural Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also reported that cultural factors such as women's delivery preferences and how the placenta is handled after the birth can significantly influence women's decisions on place of delivery [35,38,43]. In the present study, a common theme that emerged was that health facilities were not supportive of women's delivery preferences (i.e., squatting) and as a result, women did not feel that they could or that they wanted to deliver at these facilities.…”
Section: Social and Cultural Factorsmentioning
confidence: 99%
“…In this study, out of pocket costs were a significant factor that negatively influenced utilization of health facilities for delivery. Research has reported that in LMICs the costs associated with health facility delivery dissuaded women from using these facilities due to the financial burden that this imposed on the family [25,26,28] and that these costs were associated with home delivery persistence even in countries that had eliminated user fees for childbirth [13,43,45]. Hidden costs for drugs, supplies (i.e., gloves, syringes, kanga, kerosene, and plastic cover), referrals and transport reduced the affordability of maternal and childcare services in these disadvantaged communities.…”
Section: Economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several advantages related to the implementation of partial or total free health care have been described in the literature [1,2,[5][6][7][8][9]. It allows for financial protection of populations [7] and a reduction in household health expenditure [5,8]. It strengthens women's empowerment in health decision-making [9] and benefits the poor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Health facilities are paid prospectively according to a fee-for-service method with scheduled fees. A recent study showed that while the policy has provided effective nancial protection, a signi cant proportion of women continue to pay for services and consumables that should be free of charge [27]. Even if there is no fee attached to ANC visits and IPTp, there are still costs associated with visiting xed.…”
Section: Discussionmentioning
confidence: 99%